Jouer court et/ou jouer long ? - Hugo Juskowiak (Temporalités, 2017)
The article tries to show that accessing the highest level of football playing is linked inseparably to a range of short-term successes while at the same time, a demanding daily high level sport investment can not be sustained without projecting into a long-term career. But understanding, accepting and entering into these overlapping time frames can be built up only slowly and in stages by young football players. For some, it may never even happen. Therefore, the work of the technical staff, anxious to establish the future players’ economic and sporting value, consists, by playing with evaluation procedures and available contracts, in grasping the time frames prescribed by the French Football Federation when selecting and training the players supposed best equipped to enter the market of professional footballers.